Lactobacillus plantarum AR113 attenuates liver injury in D-galactose-induced aging mice via the inhibition of oxidative stress and endoplasmic reticulum stress - Yongjun Xia; Yujie Gong; Xiangna Lin; Yijin Yang; Xin Song; Guangqiang Wang; Zhiqiang Xiong; Yangyang Qian; Zhuan Liao; Hui Zhang; Lianzhong Ai (Food Science and Human Wellness)
Probiotics could effectively eliminate excess reactive oxygen species (ROS) generated during aging or lipid metabolism disorders, but their mechanism is unclear. The major purpose of this study was to investigate the mechanism of Lactiplantibacillus plantarun AR113 alleviating oxidative stress injury in the D-galactose induced aging mice. The result showed that pretreatment with L. plantarun AR113 significantly relieving H2O2 induced cytotoxicity in HepG2 cells by maintain cell membrane integrity and increasing antioxidant enzyme activities. In D-galactose induced aging mice, L. plantarun AR113 could significantly attenuate liver damage and inf lammatory infiltration by promoting endogenous glutathione (GSH) synthesis and activating the Nrf2/Keap1 signaling pathway in mice, and increasing the expression of regulated phase Ⅱ detoxification enzymes and antioxidant enzymes. Further analysis shown that gavage of L. plantarun AR113 could significantly reduce the expression of G protein-coupled receptor 78 (GPR78) and C/EBP homologous protein(CHOP) proteins, and promote the restoration of endoplasmic reticulum (ER) homeostasis, thereby activating cell anti-apoptotic pathways. These results were also confirmed in H2O2-treated HepG2 experiments. It indicated that L. plantarun AR113 could inhibit D-galactose-induced liver injury through dual inhibition of ER stress and oxidative stress. L. plantarun AR113 have good application potential in anti-aging and alleviating metabolic disorders.